Happy Valley. Series 3 [videorecording (DVD)] - Wainwright, Sally, 1964- (BBC Studios, 2023)
"When Sergeant Catherine discovers the remains of a gangland murder victim it sparks a chain of events that unwittingly leads her straight back to murderer and rapist Tommy Lee Royce. Meanwhile, Catherine's grandson Ryan is now sixteen and has ideas of his own about what kind of relationship he wants to have with Tommy, the man Catherine refuses to acknowledge as his father."--